Effect of Using Image Media as Media Learning Towards Skill Improvement Writing Student Poetry in Language Learning Indonesia for Elementary Student - Triana, Heny; Sutikno; Rahmat Kartolo; Hasnah Harahap, Popy; Irma Masithah (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the influence of using image media on improving poetry writing skills among Grade VI students at UPT SPF SDN 101763 Klumpang Kampung, Hamparan Perak Subdistrict, during the 2025/2026 academic year. The subjects included two classes, VIA and VIB, consisting of a total of 48 students. The study employed a quantitative pre-experimental design using the One Group Pretest-Posttest method. The research stages began with a pretest to measure the initial poetry writing skills of students. Subsequently, the students were taught using image media as visual aids. After the intervention, a posttest was conducted to evaluate learning outcomes. Statistical analysis revealed significant differences between pretest and posttest results. The findings indicate that image media significantly influenced the improvement of students' poetry writing skills. The average posttest score for VIA increased from 65.23 to 82.45, while the score for VIB rose from 64.85 to 81.78. The use of image media proved effective in helping students understand abstract concepts, stimulate imagination, and express ideas creatively in poetry. Aspects such as word choice (diction), poetry structure, and imagery showed significant improvement. In conclusion, image media is not only relevant but also highly effective in teaching poetry writing. It provides an engaging learning experience and motivates students to be more active and creative. Thus, the use of image media is recommended as an innovative approach to enhance the quality of Indonesian language learning, particularly in developing poetry writing skills